COMPOSITION AND CARBON STOCKS IN TALAGA KULON FOREST, MAJALENGKA DISTRICT, WEST JAVA PROVINCE, INDONESIA - Yayan Hendrayana; Tira Nurjanah; Agus Yadi Ismail (Faculty of Forestry and Environment, Universitas Kuningan, 2018)
The community forest in addition to the role for supplying wood and non-wood forest products industry, also play a role for carbon sinks, wich is stores into tree biomass. The species, diameter, and height are the most important properties of tress that are affecting the availability of tree biomass and carbon stock. The role of forests in carbon sinks have been gives a lot of benefits in reducing greenhouse effect which is caused global warming and climate change that also give affect to economy and environmental consequences. As the result, government of Indonesia has committed to reducing greenhouse gas emissions that clauses contained in Regulations of President of The Republic of Indonesia Number 71/2011 on the Implementation of National GHG Inventory. This research took a place at the civilian forest of Talaga Kulon, Majalengka District. Describe the aims of research The methods that are used in this research to find the dominance and the Important Value Index (IVI) value is analysis of vegetation. Mean while for finding biomass calculate I used allometric equations. The result of this research showed that the species of Mahogany, Sengon, Teak, Tisuk and any African/Mences type are the one that have the highest dominance and IVI value. While the amount of Carbon stocks of Civilian Forest of Talaga Kulon Village is 43,55 tons C/ha which composed for pole-stage tree is 9,33 tons/ha and 34,22 tons/ha for sawtimber stage tree.